Is Mass Housing Increase or Decrease Symbolic Cultural Diversity? An Emperical Investigation - Zuber Angkasa Wazir; Sandra Eka Febrina (Talenta Publisher, 2021)
Housing is one of basic needs in modern society driven by the population growth and limited land resource. Housing for low-income segment has minimum standard features which difficult personalization. Nevertheless, people have means to create personal identity symbol on facade material to show personalization in the simplest way. Purpose of this research is to investigate diversity symbol type created by housing resident despite personalization limited constraint. Transdiciplinary housing theory (Salama et al, 2017) is served as basic framework of this research. Observations conducted in five housing in Palembang discover fewer collectivism symbols and many individualism symbols. Thus author revised the transdiciplinary model and create housing social architecture model for better descriptions on how housing dweller responses to housing architecture and defines their cultural identity. Instead of tune down culture symbolism, mass housing exhibits more basic roots of this symbolism.